Covid-19 Drug Control Based on BPOM Informatorium with ABC Method at the Pharmacies of Bandung City - Agustini, Kamelia; Lestihati, Resti (Rescollacom (Research Collaborations Community), 2024)
According to statistical data from JHU CSSE COVID-19 in June 2021, there was an increase in positive cases of Coronavirus and began to decline at the end of August 2021. The planning that has been made must be corrected using the ABC method because a type of drug can consume a large budget if it is used a lot and is expensive. The purpose of this ABC value analysis is to identify the types of drugs from the scale of use that require the most costs. This type of non-experimental research uses descriptive methods through retrospective quantitative data collection using previous data, namely June – August 2021. Based on the scale of the use of Covid-19 drugs which are included in group A with the highest number of uses, it is necessary to ensure the availability of sufficient stock for avoid stock shortages that can hamper patient care in hospitals and can cause losses to hospitals. Drugs that are included in group B are adequately controlled by using warehouse stock cards and stock cards in the compounding and retail sales rooms. Drug group C needs to be controlled so that the number of drugs is not too excessive to avoid losses due to expired or damaged drugs. A review of the ABC analysis can be carried out annually along with the determination of the use of a standard drug list and the preparation of an annual budget plan.